Hospital Cost Function in a Non-Market Health Care System - Bilodeau, Daniel; Crémieux, Pierre-Yves; Ouellette, Pierre (The Review of Economics and Statistics, 2000)
This paper examines whether a competitive model of the firm appropriately describes the behavior of hospitals in a non-market environment. This test is based on the best database yet available in the hospital sector. We show that properties of the non-market hospitals' cost functions are compatible with short-term, but not long-term, cost-minimizing behavior. This is consistent with results of similar analyses in the U.S. hospital market and suggests that Québec hospitals, which operate in a non-market environment, might not behave fundamentally differently from their U.S. counterparts.